2011
DOI: 10.1177/1352458511431075
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted gait training in multiple sclerosis patients: a randomized trial

Abstract: Robot-assisted gait training is feasible and safe and may be an effective additional therapeutic option in MS patients with severe walking disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(126 citation statements)
references
References 47 publications
4
119
3
Order By: Relevance
“…In the experiment, body weight support was progressively reduced weekly, from 40% of the body weight for the first week after the beginning of the training program to 30% for the second week and 20% for the third week [5,24,25]. The participants' average forward walking speeds were 0.6-1.0 km/h and average backward walking speeds were 0.4-0.9 km/h.…”
Section: Interventionmentioning
confidence: 99%
“…In the experiment, body weight support was progressively reduced weekly, from 40% of the body weight for the first week after the beginning of the training program to 30% for the second week and 20% for the third week [5,24,25]. The participants' average forward walking speeds were 0.6-1.0 km/h and average backward walking speeds were 0.4-0.9 km/h.…”
Section: Interventionmentioning
confidence: 99%
“…Functional independence and healthrelated quality of life (HRQoL) are among the outcome measures more investigated. Some studies showed as rehabilitation can improve the motor parameters of functional independence measures (FIM) in PwMS [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…LOKOMAT is a more advanced device which consists of a treadmill relief system and a computer control system of the movement of the lower limb orthoses connected to sensors. 30 Another stimulus in the field of physiotherapy, which comprehensively acts on the body of the patient, is hydrotherapy. The physical properties of water such as hydrostatic pressure, hydrodynamic pressure, viscosity and buoyancy make the unloaded gymnastics of the motor system feasible so that it is possible to obtain a greater range of joint movement without pain components.…”
Section: Impairment-based Approachmentioning
confidence: 99%